(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the past, the Upper castes have suffered enormous socioeconomic deprivation in this segment of the Indian population. They were asked to work menial jobs for the upper castes under a contractual arrangement, for example, zajmany, to carry away dead animals’ carcass, for leather tanning, farm labour etc. They were put beyond the cast-system in a different position in the same village, in deplorable living circumstances, and refused the access to services (e.g. land and water and villages) and the skills (e.g. education). After the independence, India’s government has taken several special measures of welfare to enhance the country, including a complete ban on untouchability, making it a punishable act under the Constitution, an absolute ban on caste-based atrocities, the right of owners and farmers and the reservation of seats in education institutions (see parliament) The reservations, originally rendered for a period of ten years, have remained continued till date.